Beyond bacteria: Reconstructing microorganism connections and deciphering the predicted mutualisms in mammalian gut metagenomes. Issue 2 (22nd February 2023) - Dai, Qinlong; Ding, Jingjing; Cui, Xinyuan; Zhu, Yudong; Chen, Hua; Zhu, Lifeng
Abstract: Numerous gut microbial studies have focused on bacteria. However, archaea, viruses, fungi, protists, and nematodes are also regular residents of the gut ecosystem. Little is known about the composition and potential interactions among these six kingdoms in the same samples. Here, we unraveled the complex connection among them using approximately 123 gut metagenomes from 42 mammalian species (including carnivores, omnivores, and herbivores). We observed high variation in bacterial and fungal families and relatively low variation in archaea, viruses, protists, and nematodes. We found that some fungi in the mammalian intestine might come from environmental sources (e.g., soil and dietary plants), and some might be native to the intestine (e.g., the occurrence of Neocallimastigomycetes ). The Methanobacteriaceae and Plasmodiidae families (archaea and protozoa, respectively) were predominant in these metagenomes, whereas Onchocercidae and Trichuridae were the two most common nematodes, and Siphoviridae and Myoviridae the two most common virus families in these mammalian gut metagenomes. Interestingly, most of the pairwise co‐occurrence patterns were significantly positive among these six kingdoms, and significantly negative networks mainly occurred between fungi and prokaryotes (both bacteria and archaea). Our study revealed some inconvenient characteristics in the mammalian gut microorganism ecosystem: (1) the community formed by members of the analyzed kingdoms reflects the life history of the host and the potential threat posed by pathogenic protists and nematodes in mammals; and (2) the networks suggest the existence of predicted mutualism among members of these six kingdoms and of the predicted competition, mainly among fungi and other kingdoms. Abstract : Here, we unraveled the complex connection among them using approximately 123 gut metagenomes from 42 mammalian species (including carnivores, omnivores, and herbivores). Our study revealed the existence of predicted mutualism among members of these six kingdoms (e.g., archaea, bacteria, viruses, fungi, protists, and nematodes) and of the predicted competition were mainly among fungi and other kingdoms.